Ultra-processed products industry operating as an interest group - Aline Brandão Mariath; Ana Paula Bortoletto Martins (Universidade de São Paulo, 2020)
ABSTRACT The participation of the ultra-processed products industry in efforts to reduce obesity and diet-related non-communicable diseases has been questioned, especially because there is evidence of its interference in policy-making processes. This article builds on the Collective Action Theory and the literature of political science to discuss the role of this sector as a special interest group that uses its significant economic power to influence government decisions in its favor. In Brazil, its participation occurs mainly with industry associations. However, it has not yet been established whether their interests prevail in the decision-making process. It has been suggested that research should be carried out to determine the degree of success of their actions, identifying the conditions associated with the convergence of policy results with their interests and indicating to what extent civil society organizations are able to make public interests override private ones.